Providers perceptions on postpartum IUCD as an option of postpartum family planning services in India - Asif, Rashmi; Balasubramaniam, Sudharsanam Manni; Das, Saswati; Joshi, Naresh Chandra; Kumar, Somesh; Sood, Bulbul (Indian Journal of Community Health, 2017)
Background: With high unmet need for family planning in postpartum period new methods like postpartum intrauterine contraceptive device (PPIUCD) can reduce the gap between demand and supply. Role of providers is critical in facilitating a client’s decision to choose an appropriate contraceptive method during her postpartum status. Aims & Objectives: To assess the role of providers in facilitating client’s decision to choose an appropriate contraceptive method during her postpartum status. Material & Methods: This descriptive study was conducted as a multi-centric post-training PPIUCD follow up study of providers in eight states of India. From February 2012 to July 2012, 124 PPIUCD trained providers of sixteen hospitals were interviewed with a standardized questionnaire after informed consent. The providers were interviewed for their perceptions on timing and benefits of family planning counseling, procedure ease, side effects and complications of PPIUCD and their perception of client satisfaction of the method. Proportions and mean (SD) were calculated. Results: 66 doctors, 42 nurses and 16 counselors were interviewed. 95% providers felt IUCD is a suitable method for postpartum women. According to 94% doctors, 55% nurses and 88% counselors, antenatal period was the most preferred period for counselling clients. 89% doctors and 69% nurses felt that ideal time of insertion was immediately after delivery of placenta and most preferred Kelly’s placental forceps for insertion. Expulsion was the commonest perceived complication. More than 70% providers felt that clients were satisfied with their decision of choosing PPIUCD as a method with reasons. Conclusions: The results of this descriptive study on providers’ perceptions for IUCD use during the postpartum period showed a positive inclination of the interviewed PPIUCD trained doctors, nurses and counselors towards the method which will help improve access and availability to this service